Single-shot single-beam coherent Raman scattering thermometry based on optically induced air lasing - Xu Lu; Yewei Chen; Francesco Mazza; Siyi He; Zihan Li; Shunlin Huang; Quanjun Wang; Ning Zhang; Bo Shen; Yuzhu Wu; Jinping Yao; Ya Cheng (Light: Science & Applications)
Abstract Thermometric techniques with high accuracy, fast response and ease of implementation are desirable for the study of dynamic combustion environments, transient reacting flows, and non-equilibrium plasmas. Herein, single-shot single-beam coherent Raman scattering (SS-CRS) thermometry is developed, for the first time to our knowledge, by using air lasing as a probe. We show that the air-lasing-assisted CRS signal has a high signal-to-noise ratio enabling single-shot measurements at a 1 kHz repetition rate. The SS-CRS thermometry consistently exhibits precision of <2.3% at different temperatures, but the inaccuracy grows with the increase in temperature. The high measurement repeatability, 1 kHz acquisition rate and easy-to-implement single-beam scheme are achieved thanks to the unique temporal, spectral and spatial characteristics of air lasing. This work opens a novel avenue for high-speed CRS thermometry, holding tremendous potential for fast diagnostics of transient reacting flows and plasmas.